Postpartum depression and associated factors among women visiting postnatal clinic in Ethiopia - Ousman, Seman Kedir (Ethiopian Journal of Reproductive Health, 2025)
Background: Postpartum depression (PPD) is a significant public health concern in resource-scarcely sub-Saharan Africa (SSA). Despite the expanding population of those with PPD, early detection, treatment, and prevention of PPD remain a challenge in Ethiopia. The study aims to assess the magnitude and associated factors of PPD among women visiting postnatal clinic at Tirunesh Beijing Hospital, Addis Ababa, Ethiopia. Methods: A hospital-based, cross-sectional study was conducted. Depressive symptoms assessed by a locally pre-validated Edinburgh Postnatal Depression Scale (EPDS). Data was analyzed using SPSS version 26. Descriptive analysis was employed for baseline characteristics and determined the magnitude of PPD. Bivariable and multivariable regression analyses was employed to identify factors associated with PPD. Odds ratio (OR) with 95% confidence interval (CI) computed, and a p-value <0.05 considered significant. Result: In this study 24% of women experienced postpartum depression. Mothers with age 25-30 years (AOR=0.07, (95%CI: 0.02, 0.24)), women who were illiterate (AOR=4.8, (95%CI: 1.92, 14.52)), those who experienced intimate partner violence (AOR=7.1, (95%CI: 2.76, 16.12)), who had unwanted and unplanned pregnancy (AOR=6.1, (95%CI: 2.01, 13.25)), with low-birth-weight baby (AOR=3.2, (95%CI:1.29, 12.84)), and those who had poor support (AOR=3.4, (95%CI:1.40, 10.92)), within a family, were significantly associated with postpartum depression. Conclusion: The magnitude of postpartum depression was higher among mothers visiting the postnatal clinic. This highlighted the need for targeted interventions addressing the needs of postpartum women who experience various risk factors. Also, stimulates further research on risk stratification and advocacy for incorporating maternal mental health services across the different tiers of Ethiopian health care system.